2007
DOI: 10.1016/j.adolescence.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of multigroup ethnic identity measure (MEIM) scores with Australian adolescents from diverse ethnocultural groups

Abstract: The present study investigated the reliability and factor structure of scores on a 12‐item version of Phinney's multigroup ethnic identity measure with an Australian sample from diverse cultural backgrounds. Participants were 485 students aged between 10 and 15 years. The results generally supported the reliability of the ethnic identity scale scores and suggested a two‐factor structure of ethnic identity consisting of Affirmation/Belonging, and Exploration. Results concerning the other group orientation scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
(64 reference statements)
4
36
1
4
Order By: Relevance
“…The two-factor structure continues to be tested. Some studies with adolescents (Dandy, Durkin, McEvoy, Barber, & Houghton, 2008;Gazis, Connor, & Ho, 2010;Pegg & Plybon, 2005;Spencer, Icard, Harachi, Catalano, & Oxford, 2000;Yancey, Aneshensel, & Driscoll, 2001) and adults (Avery, Tonidandel, Thomas, Johnson, & Mack, 2007;Yoon, 2011) have supported this structure, while other studies have not. An analysis of adolescent data in Zimbabwe supported a one-factor solution (Worrell, Conyers, Mpofu, & Vandiver, 2006).…”
Section: Psychometric Testing Of the Meim With Diverse Populationsmentioning
confidence: 79%
See 1 more Smart Citation
“…The two-factor structure continues to be tested. Some studies with adolescents (Dandy, Durkin, McEvoy, Barber, & Houghton, 2008;Gazis, Connor, & Ho, 2010;Pegg & Plybon, 2005;Spencer, Icard, Harachi, Catalano, & Oxford, 2000;Yancey, Aneshensel, & Driscoll, 2001) and adults (Avery, Tonidandel, Thomas, Johnson, & Mack, 2007;Yoon, 2011) have supported this structure, while other studies have not. An analysis of adolescent data in Zimbabwe supported a one-factor solution (Worrell, Conyers, Mpofu, & Vandiver, 2006).…”
Section: Psychometric Testing Of the Meim With Diverse Populationsmentioning
confidence: 79%
“…The small number of the items in the subscale partially contributed to the lower alpha. However, studies using the 12-item MEIM reported similar levels of Cronbach's alpha for Exploration (5 items) and Commitment (7 items); for instance, 0.70 and 0.84, respectively (Roberts et al, 1999), and 0.74 and 0.83, respectively (Dandy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Identity commitment is characterized by pos itive affirmation of one's own ethnic group membership and a sense of belonging or attachment to that group. This twodimension structure for the MEIM has received empirical support using diverse samples from the United States (e.g., Pegg & Plybon, 2005;Spencer, Icard, Harachi, Catalano, & Oxford, 2000;Yancey, Aneshensel, & Driscoll, 2001) and other countries (e.g., Dandy, Durkin, McEvoy, Barber, & Houghton, 2008).…”
Section: The Multigroup Ethnic Identity Measure (Meim)mentioning
confidence: 99%
“…Firstly, there is support for at least two hypothesized components of ethnic identity; one reflecting the developmental status of an individual (e.g. exploration of versus commitment to an identity), and the other reflecting an affective component, for example, pride in belonging (Dandy, Durkin, McEvoy, Barber, & Houghton, 2008;Phinney Horenczyk, Liebkind, & Vedder, 2001;Umaña-Taylor, 2004;Verkuyten, 2005). Secondly, most members of minority ethnic groups in multi-ethnic contexts report stronger identification with the minority identity than with the majority culture, although the two dimensions are not mutually exclusive and many individuals report what acculturation researchers refer to as an integrated or bicultural identity (Hutnik, 1991;LaFromboise, Coleman, & Gerton, 1993;Phinney et al, 2001).…”
Section: Introductionmentioning
confidence: 98%